COMPARAÇÃO DO ESTADO NUTRICIONAL DOS ADOLESCENTES DO ESTADO DO MARANHÃO UTILIZANDO AS CLASSIFICAÇÕES DE CONDE E MONTEIRO E DA WORLD HEALTH ORGANIZATION - Costa, Andréa Suzana Vieira (2011)
Adolescence according to World Health Organization (WHO) is defined as the age group between 10-19 years old. This period is marked by deep transformations, by intense growth and development and morphological and physiological changes. It was conducted a crosssectional study aiming to know the nutritional status of adolescents in Maranhão State, in the period from July 2007 to January 2008 with a representative sample of 1256 adolescents in Maranhão State. The results revealed that, among the adolescents interviewed, 51.4% lived in urban area, (50.4%) with five to eight years of study and 8.1% used pesticides in farming. Regarding the consumption of alcoholic beverages (79.6%) said they did not consume and (96.0%) who did not smoke and had family income less than minimum wage (41%). According to dwelling conditions (54.7%) had brick houses, using water of public consumption (58.7%), regarding to the excreta destiny and garbage, the septic tank (34.8%) and garbage collection (45.9%) were mentioned more frequently. When performed the association between the BMI with the socioeconomic variables there was a significant effect (p <0.05) in the variables gender, drink and income in relation to the BMI classification used. It was used classification of World Health Organization (2000) and Conde and Monteiro (2006) to define the nutritional status, when compared the adolescents BMI into two classification criteria (Conde and Monteiro and World Health Organization), it was observed a depending relation on the classification kind (World Health Organization and Conde and Monteiro) of males adolescent BMI. In the WHO criteria were found these differences in undernutrition and obesity and the criteria of Conde and Monteiro these differences were regarding to healthy weight and overweight in males. It was observed that generally there is not a significant disagreement between these two classifications, namely from WHO and Conde and Monteiro, p = 0.1637. And there is a significant correlation between the two classifications. However, the nutritional data are important individual and population parameters to guide and develop the implementation and deployment of programs that promote sustainable development that has as axis the reduction of social and economic unequalities.